2017
DOI: 10.1063/1.4999376
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling protein folding mechanism by analyzing the hierarchy of models with increasing level of detail

Abstract: Taking protein G with 56 residues for a case study, we investigate the mechanism of protein folding. In addition to its native structure possessing α-helix and β-sheet contents of 27% and 39%, respectively, we construct a number of misfolded decoys with a wide variety of α-helix and β-sheet contents. We then consider a hierarchy of 8 different models with increasing level of detail in terms of the number of entropic and energetic physical factors incorporated. The polyatomic structure is always taken into acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 56 publications
3
44
0
Order By: Relevance
“…The denaturing action of ethanol is not as simple to rationalize because polypeptide chains, in aqueous solution with high concentrations of ethanol, populate conformations having a high content of α helices 7 . A similar scenario emerged from two recent numerical studies 8,9 using an approximate, albeit accurate, method to compute the solvation free energy. It was observed that, although the native state of globular proteins is the most stable in water compared with any other competing folds having the same sequence, this is no longer the case in ethanol and in cyclohexane, where the most stable folds are those having a high content of α helices, in agreement with experimental studies.…”
Section: Introductionmentioning
confidence: 78%
“…The denaturing action of ethanol is not as simple to rationalize because polypeptide chains, in aqueous solution with high concentrations of ethanol, populate conformations having a high content of α helices 7 . A similar scenario emerged from two recent numerical studies 8,9 using an approximate, albeit accurate, method to compute the solvation free energy. It was observed that, although the native state of globular proteins is the most stable in water compared with any other competing folds having the same sequence, this is no longer the case in ethanol and in cyclohexane, where the most stable folds are those having a high content of α helices, in agreement with experimental studies.…”
Section: Introductionmentioning
confidence: 78%
“…However, it is canceled out by an increase in the sum of protein-water and water-water interaction energies. Our analyses showed that the increase is larger than the decrease (we note that many of protein-water HBs are lost upon protein folding) (Hayashi et al 2017;Hayashi et al 2018;Yasuda et al 2012;Yoshidome et al 2008).…”
Section: Folding Mechanism Of a Water-soluble Proteinmentioning
confidence: 72%
“…Our theoretical method for membrane proteins has been developed on the basis of the progress made by Kinoshita and coworkers for water-soluble proteins (Harano and Kinoshita 2005;Hayashi et al 2017;Hayashi et al 2018;Kinoshita 2009a;Kinoshita 2009b;Kinoshita 2013;Murakami and Kinoshita 2016;Oshima and Kinoshita 2013;Oshima and Kinoshita 2015;Yasuda et al 2012;Yasuda et al 2010;Yoshidome et al 2008). A water-soluble protein is immersed in water molecules which energetically move around.…”
Section: Folding Mechanism Of a Water-soluble Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Hayashi et al found that while proteins have well-defined unique structures in water, this is generally not the case in other non-polar solvents. 5,6 The stability of single polar and hydrophobic amino acids in water and non-polar solvents have also been studied (unpublished results). To close the triangle of life, the stability of B-DNA under non-aqueous conditions has also been recently assessed.…”
Section: Introductionmentioning
confidence: 99%